PENGGUNAAN MEDIA KARTU DALAM PEMBELAJARAN BAHASA JEPANG UNTUK PENINGKATAN HASIL BELAJAR SISWA KELAS XI IPA 5 SMAN 1 RENGAT - Maya Indah Wahyuni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
The research is aimed to see and give the description whether the using of card as a learning media can increase the students` achievement in learning japanese language this research design uses action research that consists of two cycles. Every cycle consists of plan, action, observation, and reflection. The instrument used to know the students` activity during the teachung and learning process.This research consists of two cycles. Every cycle consits of four meetings. If there is a weakness in the first cycle, it result will be repaired in the second cycle. The result of the research is that 1, 56% students listens teacher`s explanation, 14, 06 % students take note from the tacher`s explanation, 44, 53 % students give opinion, 23, 44 % students ask questions, and 43, 34 % students answer the questions. By using card as media in learning process, it is hoped that the students will be motivated and interested in learning japanese language.Key words : media card, development of the result learning